2014
DOI: 10.7314/apjcp.2014.15.22.9791
|View full text |Cite
|
Sign up to set email alerts
|

Gene Microarray Assessment of Multiple Genes and Signal Pathways Involved in Androgen-dependent Prostate Cancer Becoming Androgen Independent

Abstract: To study the gene expression change and possible signal pathway during androgen-dependent prostate cancer (ADPC) becoming androgen-independent prostate cancer (AIPC), an LNCaP cell model of AIPC was established using flutamide in combination with androgen-free environment inducement, and differential expression genes were screened by microarray. Then the biological process, molecular function and KEGG pathway of differential expression genes are analyzed by Molecule Annotation System (MAS). By comparison of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Plasma‐derived cfDNA found in an individual is largely contributed by tissue DNA being shed into the blood stream due to necrosis and apoptosis . While healthy individuals have very low cfDNA amount in the plasma, cancer patients tend to have increased levels of cfDNA and patients with more aggressive and/or metastatic cancer have even higher levels of plasma‐derived cfDNA . Studies have shown that the blood of cancer patients contains cfDNA that matches specific DNA mutations and chromosomal translocations originally present in primary tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma‐derived cfDNA found in an individual is largely contributed by tissue DNA being shed into the blood stream due to necrosis and apoptosis . While healthy individuals have very low cfDNA amount in the plasma, cancer patients tend to have increased levels of cfDNA and patients with more aggressive and/or metastatic cancer have even higher levels of plasma‐derived cfDNA . Studies have shown that the blood of cancer patients contains cfDNA that matches specific DNA mutations and chromosomal translocations originally present in primary tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed using Molecule Annotation System (MAS) V3.01 (CapitalBio Corp., Beijing, China). MAS provides a series of comprehensive functional annotation tools to elucidate the biological meaning of differentially expressed genes ( 23 ). GO is the product of a collaborative effort to address the need for consistent descriptions of gene products among several databases and covers the following three domains: Biological Process, Cellular Component and Molecular Function.…”
Section: Methodsmentioning
confidence: 99%
“…The primary reasons for ADPC becoming AIPC are gene expression variation, signal pathway abnormity, and dysregulation of proto-oncogenes, cancer suppressor genes and growth factors (4). At present, studies have identified a large number of relevant genes and signal pathways of prostate cancer (5)(6)(7). However, since the biological behavior of prostate cancer is extremely complex, any of the aforementioned hypotheses cannot clarify the pathogenetic mechanism of AIPC (6).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the biological behavior of prostate cancer is extremely complex, any of the aforementioned hypotheses cannot clarify the pathogenetic mechanism of AIPC (6). Therefore, identification of genes involved in the transition from ADPC to AIPC is important to extend the current knowledge of AIPC (7).…”
Section: Introductionmentioning
confidence: 99%